The bisphenol S contamination level observed in human follicular fluid affects the development of porcine oocytes - Žalmanová, Tereza; Hošková, Kristýna; Prokešová, Šárka; Nevoral, Jan; Ješeta, Michal; Benc, Michal; Yi, Young-Joo; Moravec, Jiří; Močáryová, Beáta; Martínková, Stanislava; Fontana, Josef; Elkalaf, Moustafa; et al. (Frontiers in Cell and Developmental Biology, 2023)
Bisphenol S (BPS) is the main substitute for bisphenol A, and its detrimental effects on the reproduction of animals, including humans, have been thoroughly proven. In our study, we demonstrated the presence of BPS in the follicular fluid of women at a concentration of 22.4 nM. The effect of such concentrations of bisphenol S on oocyte maturation and subsequent embryo development is still unknown. Therefore, we focused on the effect of bisphenol S on in vitro oocyte maturation, fertilization, and embryo development. As a model, we used porcine oocytes, which show many physiological similarities to human oocytes. Oocytes were exposed to bisphenol S concentrations similar to those detected in female patients in the ART clinic. We found a decreased ability of oocytes to successfully complete meiotic maturation. Mature oocytes showed an increased frequency of meiotic spindle abnormalities and chromosome misalignment. Alarming associations of oocyte bisphenol S exposure with the occurrence of aneuploidy and changes in the distribution of mitochondria and mitochondrial proteins were demonstrated for the first time. However, the number and quality of blastocysts derived from oocytes that successfully completed meiotic maturation under the influence of BPS was not affected.